Claude Pajon (1626-1685) and the Academy of Saumur the first controversy over grace - Gootjes, Albert (Leiden Brill, 2013)
This is the first published monograph on the Saumur theologian Claude Pajon. Drawing on manuscript sources, it examines Pajon's thought and its origins, and traces the nature and course of the first of two controversies over his theology (1665-1667)
Includes bibliographical references and index. - English. - Print version record
English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Pajon, Claude 1626-1685 -- Pajon, Claude 1626-1685; Pajon, Claude -- 1626-1685; Pajon, Claude 1626-1685 -- 1600-1699; Pajon, Claude; Church History -- 17th century; Church History -- 17th century; RELIGION ; Christian Theology ; Systematic; RELIGION ; Christianity ; General; Religion; Philosophy & Religion; Christianity; Church History; Saumur (France) -- Church history -- France -- Saumur; Saumur (France) -- Church history; France ; Saumur; Electronic books; Electronic books -- Church history